Effect of C/N/P Ratio on the Performance of a Downflow Stationary Fixed Film Reactor (DSFFR) Working at Low Organic Loading Rates - Méndez, R.; Pan, L. M.; Lema, J. M. (Water science and technology, 1989)
A diagram is given of a laboratory-scale anaerobic downward-flow fixed-film reactor used in studies on the effect of low concentrations of nutrients (nitrogen and phosphorus) on performance. The reactors were operated at 37C, with clay as the packing material. Results are summarized in tables and graphs showing the effect of operation with different carbon:nitrogen:phosphorus ratios. A balanced reactor gave more stable operation than one with a low nitrogen content. The liquor in the balanced reactor had a low bacterial content, mainly of individual cocci. The nitrogen-deficient unit contained mainly aggregated cocci, and the phosphorus deficient unit contained mainly filamentous bacteria.